Laminated solar cell and preparation method thereof, cell module and photovoltaic system
By adding passivating agent and recrystallization additive to the perovskite absorbing layer, the problem of low efficiency and stability of wide-bandgap perovskite solar cells is solved, and the efficient photoelectric conversion and stability of stacked solar cells is achieved, which promotes its industrialization development.
Patent Information
- Application Number
- CN202411642004.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-18
AI Technical Summary
The low efficiency and low stability of wide-bandgap perovskite solar cells limit the industrialization development of stacked solar cells.
By adding specific composition passivator and recrystallization additive to the perovskite absorber layer, the grains of the perovskite film are increased, the number of grain boundaries is reduced, the density of defect states is reduced, the phase separation phenomenon is suppressed, and the photoelectric conversion efficiency and stability are improved.
It significantly improves the photoelectric conversion efficiency and stability of stacked solar cells and promotes its industrialization development.
Smart Images

Figure CN119855361A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells and relates to a laminated solar cell and a preparation method thereof, a cell assembly and a photovoltaic system. Background Art
[0002] In order to further improve the efficiency of solar cells, connecting wide bandgap (WBG) perovskite cells in series with other cells (such as perovskite cells, crystalline silicon cells, etc.) to construct tandem solar cells is considered to be a process route with great development potential. At present, the efficiency of crystalline silicon-perovskite two-terminal tandem cells has surpassed the SQ theoretical efficiency limit of single-junction cells, and has great market prospects. However, as a sub-cell of tandem solar cells, the low efficiency and low stability of wide bandgap perovskite solar cells limit the further industrial development of tandem solar cells.
[0003] Therefore, how to improve the photoelectric conversion efficiency and stability of stacked solar cells is a technical problem that needs to be solved urgently to promote its industrial development. Summary of the invention
[0004] The present invention provides a stacked solar cell. By adding a passivator and a recrystallization additive of a specific composition into a perovskite light-absorbing layer, the grain size of the perovskite film is increased, the number of grain boundaries is reduced, the defect state density is lowered, and the occurrence of phase separation in the wide-bandgap perovskite film is suppressed, so that the stacked solar cell has excellent photoelectric conversion efficiency and stability.
[0005] The present invention also provides a method for preparing a laminated solar cell, wherein the preparation method provided by the present invention uses a special recrystallization solution and a passivating agent to recrystallize the perovskite layer, wherein the thiocyanate ions or acetate ions in the recrystallization solution can increase the grains of the perovskite film, reduce the number of grain boundaries, reduce the defect state density, thereby reducing non-radiative recombination, improving device efficiency, and also helping to inhibit phase separation and improve device stability. During the process of grain regrowth, the alkali metal ions in the passivating agent can penetrate into the bulk phase of the perovskite film under the action of gravity, fully passivate it, and thereby improve the efficiency and stability of the device.
[0006] The present invention also provides a battery assembly, which includes the stacked solar cell and thus has excellent device efficiency and stability.
[0007] The present invention also provides a photovoltaic system, which comprises the above-mentioned battery assembly.
[0008] In one aspect, the present invention provides a tandem solar cell, the tandem solar cell comprising a perovskite top cell, the perovskite top cell comprising a perovskite light absorbing layer;
[0009] The perovskite light absorbing layer comprises a perovskite material, a passivating agent and a recrystallization additive;
[0010] The perovskite material includes bromine element, the passivating agent includes alkali metal salt, and the recrystallization additive includes thiocyanate and / or a compound containing acetate.
[0011] The stacked solar cell as described above, wherein the alkali metal salt comprises one or more of potassium iodide, potassium hexafluorophosphate, and potassium thiocyanate;
[0012] And / or, the thiocyanide includes one or more of potassium thiocyanate, guanidine thiocyanate, and methylamine thiocyanate;
[0013] And / or, the acetate-containing compound includes one or more of rubidium acetate, potassium acetate, formamidine acetate, and methylamine acetate.
[0014] The stacked solar cell as described above, wherein the mass ratio of the passivator to the recrystallization additive is 1:20 to 6:1.
[0015] In the stacked solar cell as described above, the passivator is potassium iodide, the recrystallization additive is methylamine thiocyanate, and the mass ratio of the passivator to the recrystallization additive is 1:4 to 2:1.
[0016] In the stacked solar cell as described above, the thickness of the perovskite light-absorbing layer is 600-1200 nm.
[0017] The tandem solar cell as described above, wherein the bottom cell of the tandem solar cell comprises one or more of a crystalline silicon cell, a perovskite cell, a copper indium gallium selenide cell, and an organic photovoltaic cell;
[0018] Preferably, the bottom cell and the top cell have a velvet structure;
[0019] More preferably, the velvet size of the velvet structure is 100 nm to 10 μm.
[0020] In another aspect, the present invention provides a method for preparing the stacked solar cell as described above, comprising the following steps:
[0021] A perovskite film including bromine element is prepared on the hole transport layer;
[0022] A recrystallization solution including a passivating agent and a recrystallization additive is coated on the surface of the perovskite film to obtain the perovskite light absorbing layer.
[0023] The preparation method as described above, wherein the perovskite film including the perovskite material is prepared on the hole transport layer, comprises:
[0024] An inorganic salt layer including lead iodide is formed by dry deposition on the hole transport layer, and an organic amine salt is coated or deposited on the surface of the inorganic salt layer to form the perovskite film.
[0025] In the preparation method described above, the dry deposition is completed by thermal evaporation, and the conditions of the thermal evaporation are: vacuum degree ≤ 5×10 -4 Pa, the deposition rate of lead iodide is 0.5-8 Å / s, preferably 2-4 Å / s.
[0026] In the preparation method as described above, the concentration of the passivating agent in the recrystallization solution is 0.2-3 mg / mL;
[0027] And / or, the concentration of the recrystallization additive in the recrystallization solution is 0.5-4 mg / mL.
[0028] The preparation method as described above, coating the organic amine salt on the surface of the inorganic salt layer to form the perovskite film, comprises: first spin coating the organic amine salt solution on the surface of the inorganic salt layer, and then performing a first annealing treatment on the formed coating layer to obtain the perovskite film; preferably, the first spin coating speed is 1000-3000 rpm, the acceleration is 500-2000 rpm / s, and the spin coating time is 20-40s;
[0029] Alternatively, depositing an organic amine salt on the surface of the inorganic salt layer to form the perovskite film comprises: depositing the organic amine salt on the surface of the inorganic salt layer by thermal evaporation, and then performing a first annealing treatment on the formed deposited layer to obtain the perovskite film;
[0030] The temperature of the first annealing treatment is 120-180°C, and the time is 10-30 min.
[0031] The preparation method as described above, wherein the recrystallization solution including the passivating agent and the recrystallization additive is applied to the surface of the perovskite film to obtain the perovskite light absorbing layer, comprises:
[0032] Spreading the recrystallization solution on the surface of the perovskite film, and sequentially performing a second spin coating process and a second annealing process to obtain the perovskite light absorbing layer;
[0033] Preferably, the rotation speed of the second spin coating process is 3000-5000 rpm, the acceleration is 3000-5000 rpm / s, and the spin coating time is 10-30 s; the temperature of the second annealing process is 80-120° C., and the time is 10-30 min.
[0034] In the preparation method as described above, the step of preparing the recrystallization solution comprises: dissolving the passivating agent and the recrystallization additive in an alcohol solvent to obtain the recrystallization solution;
[0035] Preferably, the alcohol solvent includes one or more of isopropanol, ethanol, n-butanol and n-pentanol.
[0036] In another aspect, the present invention provides a battery assembly, comprising the stacked solar cell as described above or the stacked solar cell manufactured by the manufacturing method as described above.
[0037] In another aspect, the present invention provides a photovoltaic system, comprising the battery assembly as described above.
[0038] The implementation of the present invention has at least the following beneficial effects:
[0039] 1) The stacked solar cell provided by the present invention improves the film quality of the wide-bandgap perovskite material by adding a recrystallization additive and a passivator to the perovskite light-absorbing layer of the perovskite top cell, wherein the thiocyanate or acetic acid compound in the recrystallization additive can increase the grain size of the perovskite material, reduce the number of grain boundaries, reduce the defect state density, thereby reducing non-radiative recombination, and improving the device efficiency, while helping to inhibit the occurrence of phase separation and improve the stability of the perovskite light-absorbing layer. The alkali metal ions in the passivator can penetrate into the bulk phase of the perovskite film under the action of gravity, passivate the bulk phase defects, inhibit the occurrence of phase separation, and thereby improve the photoelectric conversion efficiency and stability of the stacked solar cell.
[0040] 2) The preparation method of the laminated solar cell provided by the present invention can induce the regrowth of perovskite grains and slow down the crystallization rate of perovskite by using a recrystallization solution including a passivating agent and a recrystallization additive to recrystallize the perovskite film, thereby increasing the grain size of the perovskite film, reducing the number of grain boundaries, and thus reducing the defect state density, reducing non-radiative recombination, and improving device efficiency. It is also beneficial to inhibit the occurrence of phase separation and improve the stability of the device. In particular, when dry deposition is used, conformal deposition of perovskite film can be achieved, which is more compatible with existing commercial silicon substrates and has more advantages in the future industrialization path. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0042] Figure 1 A schematic diagram of the structure of a stacked solar cell according to an embodiment of the present invention;
[0043] Figure 2 This is a PL test image of the perovskite light absorbing layer of Comparative Example 1;
[0044] Figure 3 This is a PL test image of the perovskite light absorbing layer of Example 1;
[0045] Figure 4 is a SEM image of the perovskite light absorbing layer of Comparative Example 1;
[0046] Figure 5 This is the SEM image of the perovskite light-absorbing layer of Example 1.
[0047] Description of reference numerals:
[0048] 100: Perovskite top cell;
[0049] 101: hole transport layer;
[0050] 102: Perovskite light absorbing layer;
[0051] 103: electron transport layer;
[0052] 104: transparent conductive layer;
[0053] 105: metal electrode layer;
[0054] 200: middle interconnection layer;
[0055] 300: bottom battery. DETAILED DESCRIPTION
[0056] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] Tandem solar cells are a highly efficient photovoltaic technology that maximizes the use of different parts of the solar spectrum by stacking multiple layers of semiconductor materials with different band gaps. Each layer of material is specifically designed to absorb light in a specific wavelength range, thereby improving the overall energy conversion efficiency. This design can significantly exceed the efficiency limit of traditional single-junction solar cells. Perovskite materials have very high light absorption capabilities and can absorb most of the incident light in a thin film layer. The band gap can also be adjusted by changing the chemical composition of the perovskite to optimize the absorption of the solar spectrum. Its many advantages make perovskite-based tandem solar cells a research hotspot in the photovoltaic field.
[0058] Wide-bandgap perovskite materials are suitable for constructing the top layer of stacked solar cells. When combined with narrow-bandgap materials as the bottom layer, the wide-bandgap perovskite material can absorb short-wavelength light, while the bottom layer material can absorb long-wavelength light, thereby maximizing the use of the solar spectrum.
[0059] Introducing bromine into perovskite materials can adjust the band gap of perovskite materials from about 1.5eV in pure iodide to more than 2.3eV. This band gap adjustment capability enables the top cell including the perovskite material to better utilize the high-energy part of the solar spectrum. However, the introduction of bromine will lead to uneven distribution of different halogen elements in the material, phase separation, uneven light absorption and charge transfer, accelerated material degradation, and widespread defects on the film surface and grain boundaries, resulting in increased recombination of charge carriers and reduced photoelectric conversion efficiency of solar cells.
[0060] Based on this, the first aspect of the present invention provides a stacked solar cell, including a perovskite top cell, wherein the perovskite top cell includes a perovskite light absorbing layer, and the composition of the perovskite light absorbing layer includes a perovskite material, a passivator and a recrystallization additive;
[0061] The perovskite material includes bromine element, the passivating agent includes alkali metal salt, and the recrystallization additive includes thiocyanate and / or acetate-containing compound.
[0062] Adding a recrystallization additive and a passivator to the above-mentioned light-absorbing layer of the wide-bandgap perovskite material improves the film quality of the wide-bandgap perovskite material, wherein the thiocyanate or acetic acid compound in the recrystallization additive can increase the grain size of the perovskite material, reduce the number of grain boundaries, reduce the defect state density, thereby reducing non-radiative recombination, and improving device efficiency, while helping to inhibit the occurrence of phase separation and improve the stability of the perovskite light-absorbing layer. The alkali metal ions in the passivator can penetrate into the bulk phase of the perovskite film under the action of gravity, passivate the bulk phase defects, inhibit the occurrence of phase separation, and thereby improve the photoelectric conversion efficiency and stability of the stacked solar cell.
[0063] The present invention does not specifically limit the types of the alkali metal salt in the passivating agent, and the thiocyanide and acetate-containing compounds of the recrystallization additive, which can be derived from organic salts or inorganic salts conventionally used in the art. For example, the alkali metal salt includes one or more of potassium iodide, potassium hexafluorophosphate, and potassium thiocyanate; the thiocyanide as a recrystallization additive includes one or more of potassium thiocyanate, guanidine thiocyanate, and methylamine thiocyanate; the acetate-containing compound includes one or more of rubidium acetate, potassium acetate, formamidine acetate, and methylamine acetate.
[0064] In a specific embodiment, the mass ratio of the passivator to the recrystallization additive is 1:20 to 6:1. Within the above mass ratio range, it is more conducive to forming a high-quality crystal structure, reducing grain boundary defects and non-radiative recombination, and thus improving battery efficiency. Exemplarily, the mass ratio of the passivator to the recrystallization additive can be 1:20, 1:15, 1:10, 1:5, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1 or a range consisting of any two of the above mass ratios.
[0065] The invention has been verified by experiments. When the passivator is potassium iodide, the recrystallization additive is methylamine thiocyanate, and the mass ratio of the passivator to the recrystallization additive is 1:4~2:1, the laminated battery can obtain higher photoelectric conversion efficiency and stability. Methylamine thiocyanate can play a role in recrystallization and promote the regrowth of perovskite grains. In this process, potassium ions can penetrate downward, passivate defects, stabilize halogen ions, and inhibit the occurrence of phase separation. And in the subsequent annealing process, thiocyanate and methylamine ions can react chemically and will not remain in the perovskite film in large quantities, thereby negatively affecting the stability of the perovskite film. Exemplarily, the mass ratio of potassium iodide to methylamine thiocyanate can be 1:4, 1:3, 1:1, 1:1, 2:1 or a range consisting of any two of the above.
[0066] The thickness of the perovskite light-absorbing layer has a significant impact on the light absorption efficiency, charge transfer and recombination, device stability and optical properties of stacked solar cells. Specifically, when the film is thinner, the light absorption layer is thinner, and the photogenerated carriers can reach the electrode faster, reducing the recombination loss of carriers. However, a too thin film may not be able to fully absorb the incident light, resulting in reduced light absorption efficiency, thereby affecting the short-circuit current density. It will also lead to a poor interface between the charge transfer layer and the perovskite layer, increasing interfacial recombination; in addition, a thinner film can reduce the mechanical stress of the device and thus improve the mechanical stability of the device. However, if it is too thin, the environmental stability of the film will be low and it will be easily affected by it and oxygen. Furthermore, when the film is thinner, it is beneficial to improve the optical transparency of the device, but if it is too thin, it will lead to insufficient light absorption and affect the photoelectric performance.
[0067] Based on the above considerations, the thickness of the perovskite light-absorbing layer is controlled to be 600~1200 nm. Controlling the thickness of the perovskite film within the above range is conducive to making the device have excellent light absorption efficiency, charge transport and recombination, device stability and optical properties.
[0068] Exemplarily, the thickness of the perovskite film may be 600 nm, 750 nm, 950 nm, 1000 nm, 1200 nm, or a range consisting of any two of the above values.
[0069] Figure 1FIG. 1 is a schematic diagram of the structure of a stacked solar cell according to an embodiment of the present invention. Figure 1 As shown, the stacked solar cell includes a bottom cell 300, an intermediate interconnect layer 200 and a perovskite top cell 100 stacked from bottom to top;
[0070] The perovskite top cell 100 includes a hole transport layer 101, a perovskite light absorption layer 102, an electron transport layer 103, a transparent conductive layer 104, and a metal electrode layer 105 stacked from bottom to top.
[0071] The hole transport layer 101 is responsible for transporting photogenerated holes from the perovskite light absorption layer to the electrode. The perovskite light absorption layer 102 is the core layer, responsible for absorbing light and generating electron-hole pairs. The electron transport layer 103 is responsible for transporting photogenerated electrons to the electrode. The transparent conductive layer 104 is responsible for transporting photogenerated electrons to the metal electrode. The metal electrode layer 105 is used to collect current and transmit it to the external circuit.
[0072] The composition of each of the above functional layers can refer to the conventional composition of perovskite solar cells in the art.
[0073] For example, the material of the hole transport layer 101 may be NiO x (x is between 1-2), one or more of PTAA, MeO-2PACz, 2PACz, Me-4PACz, and 4PACz.
[0074] The material of the electron transport layer 103 may be one or more of titanium dioxide (TiO2), zinc oxide (ZnO), tin oxide (SnO2), fullerene and its derivatives (such as PCBM), and polymer (such as P3HT).
[0075] The material of the transparent conductive layer 104 can be one or more common transparent conductive materials such as IZO, ITO, and AZO.
[0076] The material of the metal electrode layer 105 can be one or more of gold, silver, copper and aluminum.
[0077] The function of the intermediate interconnection layer 200 is to ensure that the holes generated by the top battery and the electrons generated by the bottom battery are effectively recombined, and the two sub-batteries are electrically interconnected. The present invention does not specifically limit the composition of the intermediate interconnection layer 200, which can be a transparent conductive layer or a polysilicon tunneling layer, etc. Specifically, the transparent conductive layer can be indium zinc oxide, indium tin oxide, etc.
[0078] The band gap of the bottom cell 300 needs to be complementary to the band gap of the perovskite top cell 100 to achieve maximum spectrum utilization. In a specific embodiment, the bottom cell includes one or more of a crystalline silicon cell, a perovskite cell, a copper indium gallium selenide cell, and an organic photovoltaic cell. It is understandable that when the bottom cell is a perovskite cell, it needs to use a narrow band gap perovskite material to achieve complementarity with the band gap of the top cell.
[0079] In a preferred embodiment, the bottom cell and the top cell have a velvet structure. The velvet structure refers to introducing tiny textures on the surface of the bottom cell and the top cell. The velvet structure can increase the path length of light on the cell surface, improve the light absorption efficiency through multiple reflections and scattering, and thus significantly improve the photoelectric conversion efficiency of the cell.
[0080] Furthermore, the size of the suede surface is 100 nm to 10 μm, more preferably 1 to 5 μm. The size of the suede surface structure refers to the depth of the introduced micro texture sunken into the surface.
[0081] At the above-mentioned micro-nanoscale size, the suede structure better matches the wavelength of the incident light to maximize the scattering and absorption of light.
[0082] A second aspect of the present invention provides a method for preparing the tandem solar cell as described above, comprising the following steps:
[0083] A perovskite film including a perovskite material is prepared on the hole transport layer;
[0084] A recrystallization solution including a passivating agent and a recrystallization additive is coated on the surface of the perovskite film to obtain a perovskite light absorbing layer.
[0085] The method for preparing a stacked solar cell provided by the present invention can induce the regrowth of perovskite grains and slow down the crystallization rate of perovskite by using a recrystallization solution including a passivator and a recrystallization additive to recrystallize the perovskite film formed by dry deposition, thereby increasing the grain size of the perovskite film, reducing the number of grain boundaries, and further reducing the defect state density, reducing non-radiative recombination, and improving device efficiency. At the same time, it is also beneficial to inhibit the occurrence of phase separation and improve the stability of the device.
[0086] The recrystallization solution can be prepared by dissolving the passivating agent and the recrystallization additive in an alcohol solvent. Specifically, the alcohol solvent includes but is not limited to one or more of isopropanol, ethanol, n-butanol, and n-pentanol.
[0087] In a preferred embodiment, the concentration of the passivating agent in the recrystallization solution is 0.2-3 mg / mL, and the concentration of the recrystallization additive is 0.5-4 mg / mL. Within the above concentration range, the defect states on the surface and interface of the perovskite film can be minimized without introducing additional defects, and the stability and photoelectric conversion efficiency of the perovskite light-absorbing layer can be significantly improved, so that the open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE) of the device are significantly improved.
[0088] In a specific embodiment, a perovskite film including a perovskite material is prepared on a hole transport layer, comprising:
[0089] An inorganic salt layer including lead iodide is formed by dry deposition on the hole transport layer, and an organic amine salt solution is coated on the surface of the inorganic salt layer to form a perovskite film.
[0090] In addition to lead iodide, the inorganic salt layer may also include cesium bromide, which can provide bromine and cesium elements to the perovskite film to increase the band gap of the perovskite material.
[0091] Dry deposition is a technology for forming thin films in a vacuum or controlled environment. Unlike wet deposition such as spin coating or dip coating, it does not rely on liquid solvents and can form a uniform thin film on the hole transport layer. It can also reduce the introduction of impurities and environmental pollution, thereby forming a high-purity thin film. This preparation method is more advantageous in the preparation of laminated solar cells with a velvet structure, and can form a highly flat perovskite film and inhibit the occurrence of surface defects.
[0092] The present invention does not particularly limit the dry deposition method, which can be selected from conventional dry deposition techniques, such as evaporation deposition, sputtering deposition, chemical vapor deposition, molecular beam epitaxy, and the like.
[0093] In a specific embodiment, the inorganic salt layer may be formed by thermal evaporation deposition.
[0094] The operation of thermal evaporation deposition includes: placing high-purity inorganic salt powder into an evaporation boat or crucible, placing the substrate and evaporation source in a vacuum chamber, sublimating the inorganic salt through resistance heating or molecular beam heating to form vapor, and finally condensing the vapor on the base to form a uniform inorganic salt layer.
[0095] In the dry deposition process, vacuum degree and deposition rate are two key factors affecting the quality of thin films. High vacuum conditions can significantly reduce the amount of oxygen, water vapor and other gas molecules in the environment, which is helpful for forming high-purity thin films, but it will also increase the cost of equipment. Experimental verification shows that controlling the vacuum degree ≤5×10 -4Pa, the lead iodide deposition rate is 0.5~8 Å / s, preferably 2~4 Å / ; while obtaining high-quality lead halide films, it also has low equipment costs and high production efficiency. When the inorganic salt layer also includes cesium bromide, the deposition rate of cesium bromide can be controlled to be 0.05~1 Å / s, preferably 0.1~0.5 Å / s.
[0096] In a preferred embodiment, the thickness of the formed inorganic salt layer is 300-600 nm. Within the above thickness range, sufficient precursor materials can be provided to react with the organic halide in the amine salt solution to form a perovskite material. At the same time, within the above thickness range, it is also beneficial to promote the full growth of perovskite crystals, form larger grains, and reduce grain boundary defects.
[0097] For example, the thickness of the inorganic salt layer can be 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, or a range consisting of any two of the above values.
[0098] The organic cation in the organic amine salt can react with the inorganic salt layer to form a perovskite compound. The present invention does not specifically limit the composition of the organic amine salt, which is usually generated by the reaction of an amine (such as methylamine, formamidine, etc.) and an acid (such as hydrogen bromide, hydrogen iodide, etc.), and can specifically be formamidine iodine, formamidine bromide, methylamine bromide, methylamine chloride, etc. It can be understood that the perovskite material of the present invention contains bromine, so at least one of the inorganic salt layer or the organic ammonium salt contains bromine.
[0099] The organic amine salt can be formed on the surface of the lead halide layer by coating or thermal deposition. In a specific embodiment, the organic amine salt solution is coated on the surface of the lead halide layer to form a perovskite film, including: first spin coating the organic amine salt solution on the surface of the lead halide, and then performing a first annealing treatment on the formed coating layer to obtain a perovskite film;
[0100] Furthermore, the rotation speed of the first spin coating is 1000~3000 rpm, the acceleration is 500~2000 rpm / s, and the spin coating time is 20~40 s. In the spin coating process, rpm stands for revolutions per minute. Among them, the spin coating speed directly affects the thickness and uniformity of the film, and the acceleration affects the distribution state of the recrystallization solution on the perovskite layer. Too high an acceleration is likely to cause the solution to splash, and too low an acceleration is not conducive to the uniform distribution of the film. Under the above spin coating conditions, it is conducive to the regulation of film thickness and uniformity.
[0101] In a specific manner, an organic amine salt is deposited on the surface of an inorganic salt layer to form a perovskite film, including: thermally evaporating the organic amine salt onto the surface of the inorganic salt layer, and then performing a first annealing treatment on the formed deposited layer to obtain a perovskite film.
[0102] The annealing treatment can promote the reaction between the organic amine salt and the inorganic salt layer to form a perovskite phase. Specifically, the temperature of the first annealing treatment during the spin coating and thermal evaporation deposition process is 120-180°C and the time is 10-30 minutes.
[0103] Appropriate moisture can regulate the crystallization of perovskite, but too high humidity will destroy the crystal structure of perovskite. Therefore, it is preferred to perform the first annealing treatment in an air atmosphere with a relative humidity of 30% to 40%.
[0104] Similarly, the recrystallization solution can also be applied to the surface of the perovskite film by spin coating. Specifically, after the perovskite film is formed, the recrystallization solution can be spread all over the surface of the perovskite film, and the perovskite light absorbing layer can be obtained after a second spin coating process and a second annealing process.
[0105] Specifically, the conditions of the second spin coating process are: a rotation speed of 3000-5000 rpm, an acceleration of 3000-5000 rpm / s, and a spin coating time of 10-30 s.
[0106] The second annealing treatment can promote the recrystallization process of the perovskite film, reduce the grain boundaries and defects of the perovskite film, and improve the crystallization quality of the film. Specifically, the temperature of the second annealing treatment is 80-120°C and the time is 10-30 minutes.
[0107] In a preferred embodiment, after the recrystallization solution is spread all over the surface of the perovskite film, it also includes a process of standing it for 5 to 20 seconds. During the standing process, under the action of gravity, the smaller alkali metal ions in the passivator can penetrate into the bulk phase of the perovskite film, even at the bottom interface, and passivate the defects on the surface and bulk phase of the perovskite film from top to bottom, thereby improving the efficiency and stability of the device. The inventors have found that the standing time of the recrystallization solution is an important factor affecting the effect of the perovskite grain size. When the standing time is less than 5 seconds, the grain size is small and the device performance is not significantly improved; when the standing time is greater than 20 seconds, the grain size is larger, but the film gradually becomes less dense, and many holes appear. The longer solvent residual time also damages the perovskite film, resulting in a downward trend in the performance of the device.
[0108] In order to avoid the influence of the presence of moisture on the formed perovskite thin film, the second annealing treatment is preferably performed in an inert gas atmosphere.
[0109] A third aspect of the present invention provides a battery assembly, comprising the stacked solar cell provided by the first aspect or the stacked solar cell manufactured by the manufacturing method of the second aspect.
[0110] Since the battery assembly includes the stacked solar cell, it has excellent stability and efficiency.
[0111] In another aspect, the present invention provides a photovoltaic system, comprising the battery assembly as described above.
[0112] Since the photovoltaic system includes the stacked solar cell, it has excellent stability and efficiency.
[0113] The stacked solar cell provided by the present invention will be specifically introduced below through specific embodiments.
[0114] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0115] Example 1
[0116] This embodiment provides a stacked solar cell, and the preparation method thereof comprises the following steps:
[0117] 1. Preparation of crystalline silicon bottom cells
[0118] 1) Use NaOH solution to corrode N-type single crystal silicon wafers to form a pyramid velvet structure on the N-type single crystal silicon wafers, and control the velvet size to 1~5 μm;
[0119] 2) Clean the N-type single crystal silicon wafer after texturing in NaOH and hydrogen peroxide, HF, hydrochloric acid and hydrogen peroxide, and HF solutions in turn, and dry with hot air;
[0120] 3) A first intrinsic amorphous silicon is prepared on the front side of the silicon wafer and a second intrinsic amorphous silicon is prepared on the back side using plasma enhanced chemical vapor deposition (PECVD), both with a thickness of 5 nm; then N-type microcrystalline silicon is deposited on the surface of the first intrinsic amorphous silicon and P-type microcrystalline silicon is deposited on the surface of the second intrinsic amorphous silicon.
[0121] 4) Deposit 100 nm of ITO on the surface of P-type microcrystalline silicon, and then screen-print a layer of silver electrode on the surface of ITO to complete the preparation of the crystalline silicon bottom cell.
[0122] 2. Preparation of intermediate interconnection layer
[0123] In 5×10 -4 Under a vacuum of 0.03 Pa, argon was used as a carrier gas and a radio frequency power source was used to sputter 20 nm of ITO on the surface of N-type microcrystalline silicon as an intermediate interconnection layer.
[0124] 3. Preparation of perovskite top cells:
[0125] 1) Substrate cleaning: The silicon substrate was ultrasonically treated with anhydrous ethanol for 30 min, dried with nitrogen, and then treated in a plasma cleaner for 8 min;
[0126] 2) Preparation of hole transport layer: 0.5 mg / mL Me-4PACz ethanol solution and 0.5 mg / mL MeO-2PACz ethanol solution were mixed in a volume ratio of 3:1 to obtain a mixed SAM solution; the mixed SAM solution was spread on the substrate, and spin-coated at 3000 rpm, 2000 rpm / s for 30 s. After the spin coating, it was annealed on a hot stage at 100°C for 10 min to obtain a hole transport layer;
[0127] 3) Preparation of perovskite light-absorbing layer
[0128] a. Preparation of inorganic salt layer: Take about 1 g of lead iodide (PbI2) and about 100 mg of cesium bromide (CsBr) and place them in the evaporation crucible respectively; -4 Under a vacuum degree of 1.5 Pa, lead iodide powder and cesium bromide powder were deposited on the surface of the hole transport layer at a rate of 2 Å / s and 0.2 Å / s, respectively, to obtain an inorganic salt layer with a thickness of about 300 nm.
[0129] b. Weigh 36.6 mg of formamidinium bromide (FABr), 28.8 mg of formamidinium iodine (FAI) and 7.8 mg of methylamine chloride (MACl), dissolve them in 1 mL of isopropyl alcohol (IPA) to prepare an amine salt solution. After standing for 4 h, spin-coat at 2700 rpm, 2000 rpm / s, 30 s. In the 3rd to 5th second of spin coating, drop 100 μL of amine salt solution on the lead halide layer. After spin coating, anneal at 150°C for 15 min in an air atmosphere with a relative humidity of 30%-40% to form a perovskite film.
[0130] c. Weigh 2 mg of methylamine thiocyanate and 1 mg of potassium iodide, dissolve them in 1 mL of IPA to prepare a recrystallization solution; take 150 μL of the recrystallization solution, spread it on the surface of the perovskite film, let it stand for 10 s, and spin-coat it at 4000 rpm, 4000 rpm / s for 20 s; after the spin coating, anneal it on a hot plate at 150°C for 20 min to obtain a perovskite light-absorbing layer with a thickness of 900 nm;
[0131] 4) Preparation of electron transport layer: ① In a vacuum of 10 -4 Pa, C was evaporated at a rate of 0.1 Å / s. 60 The powder is evaporated on the surface of the perovskite light-absorbing layer to form a C 60 As the first electron transport layer; ② Using ALD technology, C 6010-20 nm of tin oxide (SnO) is deposited on top. x ), forming the second electron transport layer. The pressure was maintained at 15 Pa, the temperature was 50-100 °C, and the purge gas was nitrogen with a flow rate of 60 sccm. Tetrakis(dimethylamino)tin (TDMASn) was used as a deposition precursor, and H2O was used as an oxygen source, both with a flow rate of 30 sccm. SnO x The growth rate of the film is about 0.1 nm / cycle.
[0132] 5) Preparation of transparent top electrode: -4 Under a vacuum degree of 1.3 Pa, argon was used as a carrier gas and a radio frequency power supply was used to sputter 100 nm of IZO on the surface of the second electron transport layer as a transparent top electrode.
[0133] 6) Preparation of metal electrode layer: -4 Under Pa conditions, a silver metal electrode layer with a thickness of 140 nm was evaporated on the transparent top electrode at an evaporation rate of 1.0 Å / s to obtain a perovskite solar cell.
[0134] Embodiments 2 to 8
[0135] Embodiments 2 to 8 provide a stacked solar cell, respectively, and the preparation method thereof is basically the same as that of Embodiment 1, except that the types of the recrystallization additive and the passivating agent are different from those of Embodiment 1:
[0136] Example 2 Based on Example 1, methylamine thiocyanate and potassium iodide were replaced with 1 mg of potassium thiocyanate;
[0137] Example 3 is based on Example 1, except that methylamine thiocyanate is replaced by guanidine thiocyanate;
[0138] Example 4 Based on Example 1, methylamine thiocyanate and potassium iodide are replaced with 1 mg of rubidium acetate;
[0139] Example 5 Based on Example 1, methylamine thiocyanate and potassium iodide were replaced with 1 mg of potassium acetate;
[0140] Example 6 is based on Example 1, except that methylamine thiocyanate is replaced by formamidine acetate;
[0141] Example 7 is based on Example 1, except that methylamine thiocyanate is replaced by methylamine acetate;
[0142] Example 8 is based on Example 1, except that potassium iodide is replaced by potassium hexafluorophosphate.
[0143] Embodiments 9 to 13
[0144] Embodiments 9 to 13 provide a stacked solar cell, respectively, and the preparation method thereof is basically the same as that of Embodiment 1, except that the concentration of the recrystallization additive is different from that of Embodiment 1:
[0145] Example 9 The concentration of methylamine thiocyanate was adjusted to 0.5 mg / mL, and the mass ratio of the passivating agent to the recrystallization additive was 2:1;
[0146] Example 10 The concentration of methylamine thiocyanate was adjusted to 4 mg / mL, and the mass ratio of the passivating agent to the recrystallization additive was 1:4;
[0147] Example 11 The concentration of potassium iodide was adjusted to 0.2 mg / mL, and the mass ratio of the passivating agent to the recrystallization additive was 1:10;
[0148] Example 12 The concentration of potassium iodide was adjusted to 3 mg / mL, and the mass ratio of the passivating agent to the recrystallization additive was 3:2;
[0149] Example 13: The concentration of methylamine thiocyanate was adjusted to 0.5 mg / mL, the concentration of potassium iodide was adjusted to 1.5 mg / mL, and the mass ratio of the passivator to the recrystallization additive was 3:1.
[0150] Embodiment 14-15
[0151] Embodiments 14 and 15 provide a stacked solar cell, respectively, and the preparation method thereof is basically the same as that of Embodiment 1, except that the thickness of the perovskite light absorbing layer is different from that of Embodiment 1:
[0152] The thickness of the perovskite light absorbing layer of Example 14 is 600 nm;
[0153] The thickness of the perovskite light-absorbing layer of Example 15 is 1200 nm.
[0154] Example 16
[0155] This embodiment provides a stacked solar cell, and its preparation method is basically the same as that of Embodiment 1, except that the preparation process of the perovskite light absorbing layer is:
[0156] 1) Preparation of inorganic salt layer: 548.8 mg of lead iodide (PbI2), 187.2 mg of lead bromide (PbBr2), and 28.7 mg of cesium chloride (CsCl) were dissolved in 1 mL of a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the volume ratio of DMF to DMSO was 9:1, to prepare an inorganic salt precursor solution, which was placed on a 40-50 °C hot plate and heated and stirred for 4 h. 100 µL of the inorganic salt precursor solution was taken and spread on the surface of the hole transport layer substrate, and spin-coated at 1500 rpm, 750 rpm / s for 30 s. After the spin coating, it was annealed on a 70 °C hot plate for 1 min to form a yellow transparent inorganic salt layer.
[0157] 2) Preparation of perovskite light-absorbing layer: Take 102 mg of formamidinium iodide (FAI), 10.2 mg of methylamine chloride (MACl) and 10.2 mg of methylamine bromide (MABr), dissolve them in 1 mL of isopropanol (IPA) to prepare an amine salt solution, and let it stand for 4 hours. Take 150 µL of the prepared amine salt solution, spin-coat it on the surface of the inorganic salt layer at 1700 rpm, 1000 rpm / s, 30 s, and drop it onto the surface of the lead halide substrate in the 3rd to 5th s after the spin coating. After the spin coating is completed, anneal it on a hot stage at 150 ° C for 15 minutes (annealing atmosphere is dry air) to form a perovskite light-absorbing layer.
[0158] Comparative Example 1
[0159] This comparative example provides a stacked solar cell, and its preparation method is basically the same as that of Example 1, except that: in the preparation of the perovskite light absorbing layer, step c is omitted, and the perovskite film formed in step b is used as the perovskite light absorbing layer.
[0160] Comparative Example 2
[0161] This comparative example provides a stacked solar cell, and its preparation method is basically the same as that of Example 1, except that: in the preparation of the perovskite light-absorbing layer, 2 mg of methylammonium thiocyanate and 1 mg of potassium iodide are replaced with 3 mg of methylammonium thiocyanate in step c.
[0162] Test Case
[0163] 1. The JV (current density-voltage) test was performed on the laminated perovskite solar cells prepared in the above embodiments and comparative examples:
[0164] Test method: JV test was performed using Keithley 2400 source under simulated amplitude modulation, and 1.5 G light (100 mW / cm 2 ), the device effective area is 1 cm2 , get the JV curve, and calculate the short-circuit current density J of the battery based on the JV curve sc , open circuit voltage V oc , fill factor FF, photoelectric conversion efficiency PCE. The test results are shown in Table 1.
[0165] 2. The following performance tests were performed on the perovskite light absorbing layer in the tandem solar cells of Example 1 and Comparative Example 1:
[0166] A. PL (Photoluminescence) Test
[0167] Test method: The Edinburgh FLS1000 photoluminescence test equipment is used to test the intensity or energy distribution spectrum of light of different wavelengths formed by the perovskite light absorption layer under the excitation of light. The halogen cold light source XD-302 is used for light bath irradiation.
[0168] Figure 2 This is the PL test graph of the perovskite light absorbing layer of Comparative Example 1. Figure 3 This is the PL test diagram of the perovskite light absorbing layer of Example 1. Figure 2 It can be seen that compared with the initial state, the spectrum peak of the perovskite light-absorbing layer of comparative example 1 gradually broadens after 150 minutes of illumination, and an obvious peak appears at the low wavelength. Figure 3 It can be seen that the perovskite light absorbing layer of Example 1 has no peak separation phenomenon during the 150 min irradiation. Figure 2 and Figure 3 The comparison shows that the phase separation phenomenon of perovskite film can be suppressed after treatment with passivation agent and recrystallization additive.
[0169] B. SEM (Scanning Electron Microscope) Test
[0170] Test method: Use scanning electron microscope equipment to obtain the microscopic morphology information of the surface of the perovskite film.
[0171] Figure 4 is the SEM image of the perovskite light-absorbing layer of Comparative Example 1, Figure 5 is the SEM image of the perovskite light absorbing layer of Example 1, Figure 4 and Figure 5 It can be seen from the comparison that compared with Comparative Example 1, the perovskite grains of Example 1 are larger and the number of grain boundaries is less, which indicates that the addition of passivation agent and recrystallization additive is beneficial to improving the crystal quality of perovskite film, and the improvement of crystal quality is beneficial to promoting the improvement of device performance.
[0172] Table 1
[0173]
[0174] The following conclusions can be drawn from the data in Table 1:
[0175] 1) It can be seen from Examples 1 to 16 and Comparative Examples 1 to 2 that adding an alkali metal salt passivator to thiocyanate and / or acetate and subjecting the perovskite film to a recrystallization treatment can significantly improve the Voc and FF of the device and thus improve the performance of the device.
[0176] 2) By comparing Examples 1 to 9, it can be seen that different types of thiocyanide and acetate-containing compounds can obtain higher J sc Value, V oc value, FF value and PCE value, wherein, when the perovskite light-absorbing layer includes both methylammonium thiocyanate and potassium iodide, J sc Value, V oc The FF value and PCE value are the highest, especially the FF value and Voc value are significantly improved, which promotes the improvement of the PCE value of the stacked solar cell.
[0177] 3) By comparing Examples 9 to 13, it can be seen that the thiocyanate in the recrystallization solution is in the range of 0.5 to 4 mg / mL, the alkali metal salt is in the range of 0.2 to 3 mg / mL, and the passivation agent and the recrystallization additive maintain an appropriate mass ratio, which can enable the stacked solar cell to obtain a higher J sc Value, V oc The PCE value, FF value and PCE value, especially when the mass ratio of potassium iodide to methylammonium thiocyanate is 2:1, 1:4 and 3:2 (Examples 9, 10 and 12), the PCE value of the stacked solar cell is higher.
[0178] 4) By comparing Example 1, Example 14 and Example 15, it can be seen that when the thickness of the perovskite light absorbing layer is in the range of 600~1200nm, it has a higher J sc Value, V oc The value, FF value and PCE value are the highest, making the stacked solar cell show excellent comprehensive performance.
[0179] 5) From the comparison between Example 1 and Example 16, it can be seen that compared with dry deposition, the perovskite absorption layer formed by wet coating has poor uniformity, resulting in relatively poor performance of the manufactured stacked solar cell.
[0180] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A stacked solar cell, characterized in that: The stacked solar cell comprises a perovskite top cell, and the perovskite top cell comprises a perovskite light absorbing layer; The perovskite light absorbing layer comprises a perovskite material, a passivating agent and a recrystallization additive; The perovskite material includes bromine element, the passivating agent includes alkali metal salt, and the recrystallization additive includes thiocyanate and / or a compound containing acetate.
2. The tandem solar cell according to claim 1, characterized in that: The alkali metal salt includes one or more of potassium iodide, potassium hexafluorophosphate, and potassium thiocyanate; And / or, the thiocyanide includes one or more of potassium thiocyanate, guanidine thiocyanate, and methylamine thiocyanate; And / or, the acetate-containing compound includes one or more of rubidium acetate, potassium acetate, formamidine acetate, and methylamine acetate.
3. The tandem solar cell according to claim 1 or 2, characterized in that: The mass ratio of the passivating agent to the recrystallization additive is 1:20 to 6:
1.
4. The stacked solar cell according to claim 2, characterized in that: The passivating agent is potassium iodide, the recrystallization additive is methylamine thiocyanate, and the mass ratio of the passivating agent to the recrystallization additive is 1:4 to 2:
1.
5. The tandem solar cell according to any one of claims 1 to 4, characterized in that: The thickness of the perovskite light-absorbing layer is 600-1200 nm.
6. The tandem solar cell according to any one of claims 1 to 5, characterized in that: The bottom cell of the stacked solar cell includes one of a crystalline silicon cell, a perovskite cell, a copper indium gallium selenide cell, and an organic photovoltaic cell; Preferably, the bottom cell and the top cell have a velvet structure; More preferably, the velvet size of the velvet structure is 100 nm to 10 μm.
7. A method for preparing a stacked solar cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: A perovskite film including bromine element is prepared on the hole transport layer; A recrystallization solution including a passivating agent and a recrystallization additive is coated on the surface of the perovskite film to obtain the perovskite light absorbing layer.
8. The preparation method according to claim 7, characterized in that: The wide bandgap perovskite film prepared on the hole transport layer comprises: An inorganic salt layer including lead iodide is formed by dry deposition on the hole transport layer, and an organic amine salt is coated or deposited on the surface of the inorganic salt layer to form the perovskite film.
9. The preparation method according to claim 8, characterized in that: The dry deposition is performed by thermal evaporation, and the conditions of the thermal evaporation are: vacuum degree ≤ 5×10 -4 Pa, the deposition rate of lead iodide is 0.5-8 Å / s, preferably 2-4 Å / s.
10. The preparation method according to any one of claims 7 to 9, characterized in that: The concentration of the passivating agent in the recrystallization solution is 0.2-3 mg / mL; And / or, the concentration of the recrystallization additive in the recrystallization solution is 0.5-4 mg / mL.
11. The preparation method according to claim 8, characterized in that: The organic amine salt is coated on the surface of the inorganic salt layer to form the perovskite film, comprising: first spin coating the organic amine salt solution on the surface of the inorganic salt layer, and then performing a first annealing treatment on the formed coating layer to obtain the perovskite film; preferably, the first spin coating has a rotation speed of 1000-3000 rpm, an acceleration of 500-2000 rpm / s, and a spin coating time of 20-40s; Alternatively, depositing an organic amine salt on the surface of the inorganic salt layer to form the perovskite film comprises: depositing the organic amine salt on the surface of the inorganic salt layer by thermal evaporation, and then performing a first annealing treatment on the formed deposited layer to obtain the perovskite film; The temperature of the first annealing treatment is 120-180° C., and the time is 10-30 min.
12. The preparation method according to any one of claims 7 to 11, characterized in that: The recrystallization solution including the passivating agent and the recrystallization additive is applied to the surface of the perovskite film to obtain the perovskite light absorbing layer, comprising: Spreading the recrystallization solution on the surface of the perovskite film, and sequentially performing a second spin coating process and a second annealing process to obtain the perovskite light absorbing layer; Preferably, the rotation speed of the second spin coating process is 3000-5000 rpm, the acceleration is 3000-5000 rpm / s, and the spin coating time is 10-30 s; the temperature of the second annealing process is 80-120° C., and the time is 10-30 min.
13. The preparation method according to any one of claims 7 to 12, characterized in that: The step of preparing the recrystallization solution comprises: dissolving the passivating agent and the recrystallization additive in an alcohol solvent to obtain the recrystallization solution; Preferably, the alcohol solvent includes one or more of isopropanol, ethanol, n-butanol and n-pentanol.
14. A battery assembly, characterized in that: A tandem solar cell comprising the tandem solar cell described in any one of claims 1 to 6 or a tandem solar cell prepared by the preparation method described in any one of claims 7 to 13.
15. A photovoltaic system, characterized in that: A battery assembly comprising the battery assembly of claim 14.